2021
DOI: 10.35808/ersj/2169
|View full text |Cite
|
Sign up to set email alerts
|

Retirees’ Healthcare Needs and Satisfaction with their Coverage

Abstract: Purpose: The main objective of the paper is to assess to what extent the health care needs of the retirees in Poland are satisfied and what role the private health insurance has and might have in satisfying these needs. Design/methodology/approach: We use the data from Household Budget Survey (HBS) conducted yearly by Central Statistical Office as well as own database created on the outcomes of the survey carried out in 2018 on the representative sample of Polish seniors aged 65+ for whose households' the stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…Aspects influencing the exact valuation of healthcare services were studied in a similar way as in this work. Bielawska and Lyskawa (2021) demonstrated that age, years in education and the size of the population of the place of residence all influence the willingness to pay for medical services (in my research, only the size of the population of the place of residence proved significant). Dror et al (2007) showed the correlation between the willingness to pay for health insurance and the respondents' salaries and the education level.…”
Section: Discussionmentioning
confidence: 65%
“…Aspects influencing the exact valuation of healthcare services were studied in a similar way as in this work. Bielawska and Lyskawa (2021) demonstrated that age, years in education and the size of the population of the place of residence all influence the willingness to pay for medical services (in my research, only the size of the population of the place of residence proved significant). Dror et al (2007) showed the correlation between the willingness to pay for health insurance and the respondents' salaries and the education level.…”
Section: Discussionmentioning
confidence: 65%